Peran toleransi beragama dalam kehidupan sehari-hari: Menguatkan identitas nasional di tengah keberagaman - Fadhilah, Nayla (Maliki Interdisciplinary Journal, 2025)
Indonesia faces many challenges to maintain its unity and identity as a country with many different tribes, religions, races, and cultures. Religious tolerance amidst diversity is one of the important values that is very important to build a harmonious society. Religious tolerance does not only need to be discussed normatively, but must also be applied in everyday life. How religious tolerance can strengthen the national identity of Indonesian society is the subject of this study. This study found that the sense of nationality and social solidarity are directly influenced by the behavior of mutual respect, interfaith discussions, and strengthening the values of diversity. This study uses a literature study. Religious tolerance applied at home, school, places of worship, and the general public can help people understand each other, prevent horizontal conflict, and strengthen national unity. Therefore, it is important for all parts of society, including the government and educational institutions, to continue to instill the values of tolerance as part of the formation of national character.